Planning Of A 70 kW Solar Power Plant In Magersari Village - Anggara Trisna Nugraha; Moch Fadhil Ramadhan; Muhammad Jafar Shiddiq (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2024)
Magersari Village is one of the small villages on West Java, which is in the administrative area of Magersari Regency, this village has not been reached by the PLN electricity network, which causes disturbances for residents in carrying out activities at night. This study aims to utilize solar energy developed into electrical energy (solar power plant). One of the supporting factors this area produces is a very large solar energy potential with average daily insolation of 5.71 kWh/m²/day. In planning this solar power plant, several components consist of 376 housing units, 2 elementary school units, 3 village maternity hut units, and 1 unit of worship place. Based on the analysis and calculations results, the PV power generated to supply electrical energy in Magersari Village is 75,000 Watt Peak, generated by 375 PV modules, and the panel capacity is 200 Wp with 2 PV array placement area of 460 m². Battery Charger Regulator (BCR) used as many as 36 pieces with a capacity of 24V/80A. The number of batteries used is 219 pieces with a capacity of 24V/240Ah. The inverter used is 10 kW as many as 7 units with a voltage on the system that is 24V with a total initial investment cost for Solar Power Plant components of Rp.2,473,165,000,-